Intservqual Model di Stasiun Perpindahan Selama Masa Pandemik Covid-19 - Deslida Saidah; Honny Fiva Akira Sembiring; Lut - Mafrudoh (Institut Transportasi dan Logistik Trisakti, 2021)
An interchange station or transfer station is a train station for more than one route that allows passengers to move from one route to another without leaving the station by paying a one-way fare. The purpose of this study was to determine the level of internal service capability in the organization in the field of internal customer service at the crossing station between front-line staff and support staff during the covid 19 pandemic. The research method used was a quantitative method with an analysis of internal quality measurements using the Intservqual model and measurements based on there is a gap between the service expected by internal customers (employees of other departments) and the service they actually receive. The sample used is accidental sampling of 105 support staff and 23 front line staff. The results of the study show that there is a gap that is still in a negative position, meaning that based on each dimension of the two gaps, it is still necessary to improve internal services between front-line staff and support staff.